New insights into tricalcium silicate hydration in paste. Issue 5 (22nd October 2018) - Sowoidnich, Thomas; Bellmann, Frank; Damidot, Denis; Ludwig, Horst‐Michael
Abstract: The knowledge of the aqueous phase composition during the hydration of tricalcium silicate (C3 S) is a key issue for the understanding of cement hydration. A new in situ method of computing calcium ion concentration from the measurement of the electrical conductivity on paste was coupled to isothermal calorimetry and BET measurements to get new insights on the early hydration of C3 S. Ion concentrations of the aqueous phase are mainly dependent on the degree of hydration and the water to C3 S ratio. In the case of C3 S paste, the calcium and silicon concentrations determined at low degrees of hydration can be related to the equilibrium curve of C‐S‐H having C/S = 1.27 and named C1.27 SHy . It is expected that C1.27 SHy thermodynamically controls the aqueous phase composition at this early stage. Indeed, the formation of C1.27 SHy is quasi‐immediate when C3 S is in contact with water inducing a very rapid increase of the specific surface area that remains constant during the induction period. At higher degrees of hydration, the aqueous phase composition departs from the C1.27 SHy equilibrium curve. C1.27 SHy appears to be a metastable C‐S‐H that could be related to an intermediate phase previously reported. The quasi‐immediate precipitation of C1.27 SHy on C3 S surface explains why calcium and silicon concentrations remain low during early hydration even though C3 S is strongly undersaturated. This also agrees with the control of the end of the induction period by the nucleation and growth of more stable C‐S‐H.